Survival in patients with unresectable hepatocellular carcinoma: TCC cocktail plus TACE vs TACE alone prospective randomized clinical trial - Jie Li; Bei Lv; Li Song; Xingxing Zhang; Jian Zhang; Xiaoyi Ding; Yongqiang Liu; Tao Ye; Mengzhou Guo; Tingting Fang; Biwei Yang; Zhiying Zhao; et al. (Journal of Translational Medicine)
Abstract Background Transarterial chemoembolization (TACE) is commonly used to treat patients with unresectable hepatocellular carcinoma (HCC); however, TACE alone has demonstrated unsatisfactory survival benefits. Our previous studies suggested that TACE plus oral medication of thalidomide, carmofur and compound mylabris capsule (TCC cocktail) may be a better therapeutic option. Methods In this randomized, open-label, multicenter clinical trial, 72 treatment-naive HCC patients were randomly assigned to receive cTACE alone or cTACE plus oral TCC cocktail between July 2018 and October 2019. The primary endpoint of this trial was the 1-, 2- and 3-year overall survival (OS) rates. The second endpoints of this trial included 1-, 2- and 3-year progression-free survival (PFS) rates, objective response rates (ORR) according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST), and safety with adverse events (AEs). Results The 1-, 2- and 3-year OS rates were significantly higher in the cTACE plus TCC group than in the cTACE group (83.2% vs 54.3%, 63.1% vs 30.1%, 37.7% vs 18.1%; p = 0.008), with a significantly longer median OS (29.0 vs 15.0 months; p < 0.001). Regarding the 1-, 2- and 3-year PFS rates, HCC patients in the cTACE plus TCC group also demonstrated significantly higher rates (66.3% vs 34.4%, 35.8% vs 18.8%, 31.8% vs 15.6%; p = 0.014) and had a longer median PFS (16.0 vs 8.0 months; p < 0.001) compared with cTACE group. All treatment-related AEs were tolerated. Conclusions For patients with unresectable HCC, TACE combined with TCC cocktail was well tolerated and significantly improved clinical outcomes. Trial registration The trial was registered at https://www.chictr.org.cn/showproj.html?proj=27493 as ChiCTR1800016335 on 25th May 2018 named an open-label, multicenter, randomized, prospective clinical trial of thalidomide based triple oral regimen for low-dose maintenance therapy after TACE in advanced hepatocellular carcinoma.